PENGARUH KONDISI INDUSTRI, KETIDAKEFEKTIFAN PENGAWASAN DAN STRUKTUR ORGANISASI TERHADAP KECURANGAN LAPORAN KEUANGAN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2016 – 2018 - Ni Made Muningsih; Ni Ketut Muliati (UNHI Press, 2020)
Financial statements are a means of information that allows parties outside the company's management to find out the condition of a company. Management tries as much as possible to describe the condition of the company well, not infrequently they even manipulate the financial statements according to what they want so that motivation can lead to fraud in financial statements by the company. This study aims to determine the effect of the opportunity factor of the fraud triangle theory by Cressey (1953) using annual reports of manufacturing companies listed on the Indonesia Stock Exchange from 2016-2018. Based on the research results obtained simultaneously the independent variables, namely industry conditions, ineffectiveness of supervision, and organizational structure affect the dependent variable, namely financial statement fraud. However, only partially the industry conditions had a positive and significant impact on financial statement fraud. Evidenced by the results of t count = 3,396> t table = 1,977 and a significance value of 0,001 < 0,05. Future studies are expected to examine the pressure and rationalization factors of the fraud triangle theory, as well as examine other theories such as pentagon fraud and diamond fraud theory.